Astrakhan conscientific court: history of accession to the chamber of criminal and civil court (1828) - Sergey N., Podlesnykh (Kavkazologiya, 2024)
This is the first paper in Russian historiography that attempts to explain the mechanism of the en-try of the court of conscience founded in 1775 by Catherine II under the "Institutions for the Ad-ministration of the Provinces of the All-Russian Empire. Part One” to the local chambers of the criminal and civil courts, and to identify the reasons for such accession. The case of the Astrakhan court of conscience of 1828, stored in the funds of the Russian State Historical Archive, served as an example for the analysis. Part One” to the local chambers of the criminal and civil courts, and to identify the reasons for such accession. The case of the Astrakhan court of conscience of 1828, stored in the funds of the Russian State Historical Archive, served as an example for analysis. It is shown that the “Astrakhan case” of 1828 was a kind of precedent in a series of subsequent acces-sions of courts of conscience to local judicial chambers, starting from 1847, when the position of a judge of conscience in a particular province was retained, the court of conscience, as an independ-ent judicial institution, was closed, and its competence was transferred to the local judicial cham-ber. Particular attention is paid to the analysis of the noble community of the Astrakhan province, which, in comparison with other provinces of the Russian Empire, was small. Low noble person-nel potential is one reason for the closure of the conscientious court in Astrakhan as an independ-ent institution. The second reason that influenced the closure of the Astrakhan conscientious court was the insignificant number of litigation cases pending before the conscientious judge.